Special issue on bio-ontologies and phenotypes. Issue 1 (December 2015) - Soldatova, Larisa; Collier, Nigel; Oellrich, Anika; Groza, Tudor; Verspoor, Karin; Rocca-Serra, Philippe; Dumontier, Michel; Shah, Nigam
Abstract The bio-ontologies and phenotypes special issue includes eight papers selected from the 11 papers presented at the Bio-Ontologies SIG (Special Interest Group) and the Phenotype Day at ISMB (Intelligent Systems for Molecular Biology) conference in Boston in 2014. The selected papers span a wide range of topics including the automated re-use and update of ontologies, quality assessment of ontological resources, and the systematic description of phenotype variation, driven by manual, semi- and fully automatic means.